Управління якістю технічного обслуговування та ремонту автобусів як складова системи управління якістю обслуговування пасажирів - Дмитрієв, В.І. (Культура народов Причерноморья, 2014)
В науковій статті досліджується проблема управління якістю технічного обслуговування
та ремонту автобусів як складової системи управління якістю обслуговування пасажирів. Вирішення
проблеми підвищення якості технічного обслуговування та ремонту автобусів пропонується через
введення комплексу допоміжних заходів у дані технологічні процеси, які визначаються потребами
цільового ринку. Зокрема, запропоновано організацію на підприємствах пасажирського автомобільного
транспорту спеціальної системи внутрішнього контролінгу якості технічного обслуговування та
ремонту автобусів, яка повинна бути орієнтована на узгоджені критерії якості даних технологічних
процесів, які задовольняють як виробників, так і споживачів послуг пасажирських автомобільних
перевезень. В научной статье исследуется проблема управления качеством технического
обслуживания и ремонта автобусов как составляющей системы управления качеством обслуживания
пассажиров. Решение проблемы повышения качества технического обслуживания и ремонта автобусов
предлагается через введение комплекса дополнительных мер в данные технологические процессы,
которые определяются потребностями целевого рынка. В частности, предложено организацию на
предприятиях пассажирского автомобильного транспорта специальной системы внутреннего
контроллинга качества технического обслуживания и ремонта автобусов, которая должна быть
ориентирована на согласованные критерии качества данных технологических процессов, которые
удовлетворяют как производителей, так и потребителей услуг пассажирских автомобильных
перевозок. In the scientific article the problem of management of quality of the technical control maintenance
and repair of buses as a part of management system of quality of passenger maintenance is researched. The
processes of the technical control maintenance and repair of buses as special vehicles that perform mass
passenger automobile transportation characterize by intense rhythm of work and dynamic environment
consumer preferences for safety, reliability, comfort of this type of vehicles. The following require additional
research, firstly, of the structure and content of the technical control maintenance and repair of buses, secondly,
of the formation of management system of this processes quality that affect the reliability, efficiency and traffic
safety of the buses and passenger automobile transport in general. Solving the problem of improving the quality
of the technical control maintenance and repair of buses is offered by the introduction of additional measures in
complex of these processes, which are determined by the needs of the target market. In particular, the
organization of the special internal system of controlling of quality of the technical control maintenance and
repair of buses in enterprises of passenger automobile transport is proposed. This system of controlling should
be focused on agreed criteria of quality of the technical control maintenance and repair of buses that satisfy
both producers and consumers of services of passenger automobile transportation.